“Where have you gone?” - Durrand, Hollie (The University of Edinburgh, 2014)
Improving the quality of life for those providing care for a partner with dementia in the mid to late stages is widely accepted to be important. Few studies have attempted to explore the subjective experiences of those in the primary caregiving role of a spouse in the mid to late stages of their condition. The study aimed to gain an understanding of how spousal carers, make sense of dementia, their caregiving role and their relationship after living with the condition for a number of years. Semi-structured interviews were conducted with four spouses of partners diagnosed with a form of dementia, to allow participants to share their lived experiences of providing primary care. Interview transcripts were analysed using Interpretative Phenomenological Analysis (IPA) in order to identify recurring themes. Four main themes were identified relating to the increased amount of care they were required to provide; the conflict and ambivalent thought they experienced in defining their current role; the oscillation between what was lost and what still remains in what they now perceived as a fractured bond; and the sense of injustice that surrounded their partner’s degenerative condition. The study highlights the importance of those providing additional support to spousal caregivers to recognise their loss as ambiguous.
Exploring the lived experience of providing care for a partner in the mid to late stages of dementia using Interpretative Phenomenological Analysis
Keywords: dementia; spousal caregivers; IPA; ambiguous loss